Examining the Associations of Smoking Behavior and Obesity Among Older Adults in China: Should We Consider Food Consumption Behaviors?. (24th July 2019) - Lee, Yen-Han; Chang, Yen-Chang; Shelley, Mack; Liu, Ching-Ti
Objective: This research investigates the associations between smoking frequency and body mass index (BMI) among older adults in China with and without the inclusion of food consumption behaviors.Method: Applying three waves of the Chinese Longitudinal Healthy Longevity Survey (2009, 2012, and 2014), with 12, 312 observations from 4, 104 participants, gender-stratified panel ordered logistic regressions were performed. Food consumption included intake frequency and types of fruits, vegetables, staple food, cooking oil, and meat.Results: Among male older adults, more frequent smoking behavior was associated with lower BMI with the inclusion of food consumption behaviors. However, more frequent smoking behavior was not associated with BMI among female participants with the inclusion of food consumption behaviors. Former smoking status was not associated with BMI in all models.Discussion: The findings suggest the need of food consumption behaviors when researchers study the associations between smoking frequency and obesity. Gender gaps also should be considered.